Barbel cholera, a rare but still possible food-borne poisoning. Case report and narrative review. - Comelli, Ivan; Riccò, Matteo; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2019)
The gastro enteric toxic effects of the barbel eggs have been described up to two centuries ago, but deliberate or serendipitous ingestion of this fish product still occur, often eliciting a gastrointestinal syndrome usually known as barbel cholera. Barbel cholera is a self-limited gastrointestinal diarrheic syndrome that develops 2 to 4 hours after ingestion of the eggs, lasting up to 12-36 hours, nearly always complicated by vomiting and severe abdominal pain. The disease is usually self-limited, and the prognosis is thus benign even without hospitalization and medical treatment. Rarely, however, barbel cholera may be complicated by massive diarrhea, and the patients can develop bradycardia, oligo-anuria, and eventually hypovolemic shock. In this article we describe a rare case of barbel cholera, highlighting both the diagnostic difficulties in identifying it, and the importance of obtain an accurate history, focused on recently ingested food, thus addressing the clinical management on supportive treatment, expecting symptoms’ improvement usually within 36 hours.